Interaction between CFRP side plated to R C beams and concrete under shear action - Mahmoud, L. (CI-Premier Pte Ltd, 2017)
Externally bonding fiber reinforced plastic (FRP) sheets to strengthen the existing deficient reinforced concrete (RC) structures has become a popular technology in the last decade. With the rapid development of this new technology, many issues related to the structural performances of FRP strengthened RC elements have been studied. Among them, the study on the interfacial bond between the externally bonded FRP sheets and concrete may be the most fundamental, because it plays a key role in the composite performances and the durability of RC structures after being strengthened. In order to evaluate the interfacial bond mechanisms quantitatively and carry out numerical simulation for FRP sheets strengthened RC structures, defining an accurate bond stress-slip (t~s) relationship has become a main task among the bond issues studied in the past. The primary purpose of this paper is to propose a new methodology that enables to study the interfacial behavior of CFRP-To-concrete joints under monotonic loading. The test setup and supports were designed such that there is a direct shear at the CFRP-To-concrete interface. This paper describes the experimental setup and test parameters. Next experimental results for shear capacity, monotonic bond stress-slip behavior and mathematical formulations for stiffness of interface.